Robotic assisted hysterectomy and colpectomy as gender affirming surgery in trans men: an instructional video and perioperative considerations - Kavvadias, Tilemachos; Gosch, Emma Garcia; Heinzelmann-Schwarz, Viola (Frontiers in Surgery, 2025)
Background/objectivesThe objective of this paper is to present a method of hysterectomy and colpectomy in trans men seeking gender affirming surgery using a uterovaginal manipulator device.MethodsEighteen consecutive patients underwent robotic assisted laparoscopic hysterectomy and colpectomy as gender affirming surgery. The perioperative descriptive statistical data as well as complications were documented. An instructional video has been prepared and is provided as Supplementary Material.ResultsPatients had a median age of 28 years and a mean BMI of 23.5 ± 3.8 Kg/m2. Mean operating time was 175 ± 25 min (median 180), mean blood loss was 219 ± 142 ml (median 200) and mean hospital stay was 4.6 ± 5.9 days (median 3). Two major (one compartment syndrome which required re-surgery and one bladder injury which resolved intraoperatively) and seven minor complications occurred (5 patients with urinary retention and 2 urinary tract tract infections) occurred.ConclusionsRobotic assisted laparoscopic hysterectomy and colpectomy in trans men seeking gender affirming surgery is a feasible option, facilitated by the use of a uterovaginal manipulator device. Candidates for the procedure should be properly counseled in anticipation of possible complications.